2023
DOI: 10.3389/fendo.2023.1168687
|View full text |Cite
|
Sign up to set email alerts
|

The complex pathophysiology of bone fragility in obesity and type 2 diabetes mellitus: therapeutic targets to promote osteogenesis

Abstract: Fractures associated with Type2 diabetes (T2DM) are major public health concerns in an increasingly obese and aging population. Patients with obesity or T2DM have normal or better than normal bone mineral density but at an increased risk for fractures. Hence it is crucial to understand the pathophysiology and mechanism of how T2DM and obesity result in altered bone physiology leading to increased fracture risk. Although enhanced osteoclast mediated bone resorption has been reported for these patients, the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 160 publications
(162 reference statements)
0
5
0
Order By: Relevance
“…Moreover, factors that are secreted by bone marrow adipocytes (e.g., adipokines, pro-inflammatory and immunoregulatory cytokines, and receptor activator of nuclear factor kappa beta ligand (RANKL)) may also contribute to altered skeletal homeostasis after bone marrow adipose tissue expansion [9,45]. In addition, accumulation of senescent cells and elevated levels of oxidative stress in the bone microenvironment in obesity and T2DM are among factors that may participate in bone marrow stromal cell dysfunction and cause a shift in bone marrow stromal cell differentiation phenotype that favors adipogenesis over osteogenesis [2]. The expansion of bone marrow adipose tissue was observed in bone biopsies from obese elderly men [46].…”
Section: Interactions Between Adipose Tissue and Bone Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, factors that are secreted by bone marrow adipocytes (e.g., adipokines, pro-inflammatory and immunoregulatory cytokines, and receptor activator of nuclear factor kappa beta ligand (RANKL)) may also contribute to altered skeletal homeostasis after bone marrow adipose tissue expansion [9,45]. In addition, accumulation of senescent cells and elevated levels of oxidative stress in the bone microenvironment in obesity and T2DM are among factors that may participate in bone marrow stromal cell dysfunction and cause a shift in bone marrow stromal cell differentiation phenotype that favors adipogenesis over osteogenesis [2]. The expansion of bone marrow adipose tissue was observed in bone biopsies from obese elderly men [46].…”
Section: Interactions Between Adipose Tissue and Bone Tissuementioning
confidence: 99%
“…However, for Asians, obesity is defined as a BMI greater than or equal to 25 kg/m 2 . It is predicted that by 2030, 20% of women, 14% of men, and more than 1 billion people will be living with obesity [1][2][3]. Obesity is the most important risk factor for T2DM, which is characterized by chronic hyperglycemia, insulin resistance, and inefficient insulin secretion and action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we mention further topics to explore such as the results of murine experiments showing linagliptin and metformin protective effects against bone loss [131] (one of the pathogenic traits being metformin-induced down regulation of RAGE-JAK2-STAT1 signal transduction pathway) [132]. Also, the metabolic components other than the anomalies of glucose profile, such as obesity, chronic steatosis, and abnormal lipid status might add a supplementary influence on bone damage that may be additional to insulin resistance, hyperinsulinemia, and increased blood glycemia together with the potential impairment of mineral metabolism [133][134][135].…”
Section: Integrating Tbs To the Panel Of Bone Status Assessment In T2dmmentioning
confidence: 99%
“…Both obesity and T2DM are complex metabolic disorders of multifaceted etiology accompanied by a series of complications, including macrovascular diseases (hypertension, hyperlipidemia, heart attacks, coronary artery disease, strokes, cerebral vascular disease, and peripheral vascular disease), microvascular diseases (retinopathy, nephropathy, and neuropathy), and cancers ( 6 ). Recently, studies have shown that bone health is also compromised in people with obesity and T2DM ( 7 ).…”
Section: Introductionmentioning
confidence: 99%